Video-Based Interactive Media in Fiqih Learning in Zakat Chapter for Grade IX Students Using Canva Application - Wulandari, Rika Ayu; Hidayat, Moch. Charis; Asrori, Asrori (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2025)
The existence of media is very much needed in learning activities so that it does not tend to be monotonous and theoretical, so that it can increase students' motivation to learn and apply it in everyday life. This study aims to develop learning media by utilizing the Canva application. This study uses the Research and Development (R&D) method. The media developed is based on the zakat material for grade IX odd semester in student textbooks containing moving images, animated text, audio, visuals and soft backgrounds to create a 2-3 minute video. The validation test data on the validation test sheet concluded that the percentage obtained from the validation of material expert 1 was 80%, the percentage obtained from the validation of material expert 2 was 90%, the percentage obtained from the validation of media expert 1 was 91%, the percentage obtained from the validation of media expert 2 was 85% with high intensity score criteria. Based on the results of the validation test, it can be concluded that the learning video on the zakat material for grade IX students in the odd semester is suitable for use.